(untitled) (KASBIT Business Journal, 2021)
The advent of personal connectivity, ubiquitous computing, and sensing capabilities in present-day smartphones makes them an appealing candidate for the evolving concept of Internet-of-Things (IoT). As IoT transforms human-to-human communication to autonomous device-to-device communication within a network, smartphones are conceived as its backbone. This paper proposes a Personal Tracking Model under the realm of IoT and utilizes smartphones as a key element. We articulate the feasibility of a Personal Asset Tracking scheme that can be realized under the umbrella of IoT using a smartphone and the tagged valuables. This is realized utilizing a hybrid Bluetooth/Wi-Fi-based communication topology with two employment concepts. At a lower level, a user solely uses the Bluetooth in his smartphone to track the lost or misplaced item which is tagged with a Bluetooth token. At a higher level, the object is tagged with a hybrid Bluetooth and Wi-Fi token. The Wi-Fi token provides an IoT connectivity which results in coarse localization information while the fine-grained tracking information can be achieved through Bluetooth tracking, as in the first case. We also present a technical overview and comparison of our proposed scheme with the existing tracking solution.